RELATIONSHIP OF DOCTOR’S PERCEPTION ABOUT THE DISTRIBUTION OF BPJS PATIENT MEDICAL SERVICES TO DOCTOR'S JOB SATISFACTION AT IMELDA HOSPITAL - Lie Novita Sadeli; Ida Yustina (International Journal of Nursing and Health Services (IJNHS), 2019)
Medical services salary received by doctors at Imelda General Hospital were considered to be lacking, which resulted in the doctor's dissatisfaction. The less perception about the distribution of BPJS patient medical services seen from the results of the doctor's performance evaluation in December 2017 decreased from 80% to 76.3%. The study aimed to examine the relationship between perceptions about the distribution of the amount of medical services and job satisfaction. The cross-sectional study design was applied in this study. The study conducted at the Imelda Workers’ Hospital. Sixty-two samples consisted of 48 specialists, and 14 general practitioners were involved in this study. We use total sampling to take 62 samples, analysis using chi-square by collecting data through questionnaires. The results showed there was a relationship between the distribution of the number of medical services (p = 0.025) and the timeliness of receiving medical services BPJS patients (p = 0.015) with doctor job satisfaction (p <0.05). Perceptions about the distribution of the amount of medical services and the timeliness of receiving medical services from BPJS patient services that are not by the doctor's perception will decrease the performance of doctors as is done periodically by the Imelda Hospital medical committee team. Doctor's job satisfaction can be increased by the management's efforts to be more open to doctors regarding doctor's medical services, allowing doctors to improve their career paths, and conducting periodic evaluations of doctor satisfaction through questionnaires. Keywords: job satisfaction, doctors, medical services